Improvement of Lampung Police Services Through Siger Precision Lampung 21 (PSP-21) - MS Hasibuan; Nathan Nurdadyansyah; M. Arif Rifai; Wahyu Bintono; Doni Andrianto; Adam Japal (Journal of Digital Literacy and Volunteering, 2023)
Police services using information technology are developing rapidly. The development of this service is an instruction from the National Police Chief as the head of the police force. However, the police service does not yet have an integration feature that is able to provide the public with access to one application, so all services will be easily accessible. This research builds an integration service named Siger Presisi Police (PSP) 21. This service can be accessed using the website and mobile. In PSP 21 there are panic button service features, the latest information and other application services such as online samsat, online sim, e-yanduan, e-dumasan and skck. The results of this study indicate that the level of community satisfaction has increased as evidenced by the number of accesses made to the PSP21 application.